2013
DOI: 10.5539/ijbm.v8n5p24
|View full text |Cite
|
Sign up to set email alerts
|

The Emergence of Entrepreneurial Intentions in Indigenous Entrepreneurs: The Role of Personal Background on the Antecedents of Intentions

Abstract: The fact that models of entrepreneurship have generally been developed on a global scale has made the matter of explaining and assessing indigenous level experience rather difficult from the perspective of reliability and validity. It is therefore very important from an academic perspective to reveal such local scale entrepreneurial behaviours. Research was conducted in three stages. Personal backgrounds formed by factors such as role models, traits and experience, and contextual terms were addressed. Then clu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 76 publications
4
28
1
2
Order By: Relevance
“…The results revealed that being from an entrepreneurial family background and prior start-up experience had a very weak but statistically significant negative correlation with entrepreneurial intention (p < .01), the attitude towards becoming an entrepreneur (p < .01), perceived behavioural control (p < .01) and subjective norms (p < .01). This is contrary to earlier research that has found that entrepreneurial family background and prior self-employment experience increase the likelihood of becoming an entrepreneur (Douglas & Fitzsimmons, 2013;Uygun & Kasimoglu, 2013;Dohse & Walter, 2012). The results support those of Margues et al (2012) and Zhang et al (2013) in the sense that direct experience with the entrepreneurial behaviour or observing relatives who are entrepreneurs may expose one to the outcomes that may negatively impact on the decision to choose an entrepreneurial career.…”
Section: Resultscontrasting
confidence: 86%
See 3 more Smart Citations
“…The results revealed that being from an entrepreneurial family background and prior start-up experience had a very weak but statistically significant negative correlation with entrepreneurial intention (p < .01), the attitude towards becoming an entrepreneur (p < .01), perceived behavioural control (p < .01) and subjective norms (p < .01). This is contrary to earlier research that has found that entrepreneurial family background and prior self-employment experience increase the likelihood of becoming an entrepreneur (Douglas & Fitzsimmons, 2013;Uygun & Kasimoglu, 2013;Dohse & Walter, 2012). The results support those of Margues et al (2012) and Zhang et al (2013) in the sense that direct experience with the entrepreneurial behaviour or observing relatives who are entrepreneurs may expose one to the outcomes that may negatively impact on the decision to choose an entrepreneurial career.…”
Section: Resultscontrasting
confidence: 86%
“…It was also found that positive valuation of the entrepreneurial behaviour by people in the closer environment increases the knowledge about the entrepreneurial environment (awareness of associations, support systems and access to preferential loans), which enhances perceived behavioural control. Uygun and Kasimoglu (2013) found that experience in a particular sector enhances entrepreneurial self-efficacy which in turn positively influences entrepreneurial intentions. Similarly, Douglas and Fitzsimmons (2013) and Gird and Bagraim (2008) reported a positive relationship between prior self-employment experience and entrepreneurial intentions.…”
Section: Perceived Behavioural Controlmentioning
confidence: 98%
See 2 more Smart Citations
“…It is believed that every human action is a result of intention, and intention implies a planned behavior [9]. Entrepreneurial intention can be also defined as a mental state that directs action toward self-employment rather than corporative employment [10].…”
Section: Entrepreneurial Intentionmentioning
confidence: 99%